2004
DOI: 10.1080/00016470410001286
|View full text |Cite
|
Sign up to set email alerts
|

The impact of time of admission on major complications and mortality in patients undergoing emergency trauma surgery

Abstract: BackgroundPrevious studies have shown a relationship between time of admission to hospital and mortality rates; however, it is uncertain whether such a relationship exists for patients requiring emergency trauma surgery.Methods We included all trauma patients, except those with moderate to severe burns, who presented to a university-affiliated level 1 trauma center and underwent surgery, from 1995 until 2001 (n = 1044). We conducted univariate and multivariate analyses in which the dependent variables were in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
3
11
1
Order By: Relevance
“…A 'July effect' has been hypothesized in American studies based on influx of junior doctors rather than staff reductions, but this did not influence outcome in trauma patients. 8 Seasonal variation in outcome after hip fracture has been reported previously, with mortality peaking during winter months. 9 The present study incorporates a mixture of holiday periods during both summer and winter months and, as such, the present findings cannot be explained by a seasonal variation.…”
Section: Discussionmentioning
confidence: 70%
“…A 'July effect' has been hypothesized in American studies based on influx of junior doctors rather than staff reductions, but this did not influence outcome in trauma patients. 8 Seasonal variation in outcome after hip fracture has been reported previously, with mortality peaking during winter months. 9 The present study incorporates a mixture of holiday periods during both summer and winter months and, as such, the present findings cannot be explained by a seasonal variation.…”
Section: Discussionmentioning
confidence: 70%
“…6 Outcomes in emergency trauma surgery did not differ with patient presentation between night and day. 7 Delaying surgery until daytime hours did not affect outcomes for children with acute appendicitis. 8 And better cardiovascular outcomes were reported for night-time hemodialysis patients compared with conventional dialysis patients.…”
mentioning
confidence: 98%
“…It may seem surprising that the severity of injuries was similar in the two groups because injuries are believed to be worse at night due to more severe traffic accidents24 or more acts of violence leading to more penetrating injuries 6. However, in the study that reported this latter finding, the total incidence of penetrating trauma was much higher than in our setting18 (ie, 9.5% vs 1.5%).…”
Section: Discussionmentioning
confidence: 47%
“…One study certainly included these patients9 and another one6 possibly did, although without stating it unambiguously. However, in the first study, the condition of having being transferred had an unexpected statistically significant protective effect, somewhat contrasting with established knowledge21 and possibly betraying some selection bias.…”
Section: Discussionmentioning
confidence: 99%